1970
DOI: 10.1104/pp.46.1.64
|View full text |Cite
|
Sign up to set email alerts
|

The Time Course of Xylem Differentiation and Its Relation to Deoxyribonucleic Acid Synthesis in Cultured Coleus Stem Segments

Abstract: The relationship between DNA synthesis and wound xylem differentiation was investigated in cultured stem segments of Coleus blumei. The addition of 50 micrograms of indoleacetic acid per liter to the culture medium resulted in a 400 to 500% increase in the number of wound vessel members formed in 7 days. However, the time course of wound vessel member formation was similar in segments cultured in the presence and absence of auxin. In either case, no wound vessel members appeared before the 3rd day of culture, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1972
1972
1994
1994

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Perhaps in the Zinnia system, cells treated with auxin enter a cambium-like state after cell division but cannot proceed further without cytokinin. That cell division must precede differentiation was demonstrated in some studies (24,25). Thus, the auxin-induced expression of p48h-10 gene after cell division occurs at the same time as entry into the cambium-like state.…”
Section: Discussionmentioning
confidence: 87%
“…Perhaps in the Zinnia system, cells treated with auxin enter a cambium-like state after cell division but cannot proceed further without cytokinin. That cell division must precede differentiation was demonstrated in some studies (24,25). Thus, the auxin-induced expression of p48h-10 gene after cell division occurs at the same time as entry into the cambium-like state.…”
Section: Discussionmentioning
confidence: 87%
“…Cells immediately after isolation from the first leaves of seedlings are shown in Figure 2A. Wound vessel member formation in segments of stems or roots (1,13,15) and tracheary element formation in slices of storage tissue (5,8), in cultured callus (2,18) and in a suspension cell culture (14) have been used as experimental systems for the study of cytodifferentiation to tracheary elements. The experimental system established in this work is considered to be useful for the study of …”
Section: Resultsmentioning
confidence: 99%
“…Many workers have studied the relationship between xylogenesis and the cell cycle in cultured explants of Coleus (Comer 1978, Fosket 1970, Jerusalem artichoke (Dodds andPhillips 1977, Malawer andPhillips 1979), pea (Shininger 1978, Simpson andTorrey 1977), lettuce (Dalessandro andRoberts 1971, Turgeon 1975), and in suspension cells oi Zinnia elegans (Kohlenbach and Schmidt 1975) and Centaurea (Torrey 1975), but the nature of this relationship' remains obscure (Roberts 1976), In the previous (Fukuda and Kotnamine 19S0b) and present studies, we have attempted to solve the following three important problems in order to obtain a cotnplete understanding of the relationship using single mesophyll cells isolated frotn Zinnia elegans: I, Whether or not mitosis is a prerequisite for cytodifferentiation, 2, Whether or not DNA replication is a prerequisite for cytodifferentiation, 3, Whether the tracheary element precursor cells become committed to the new pathway of cytodifferentiation after receiving stimulation to cytodifferentiation at some particular phase of the cell cycle. We showed direct differentiation to tracheary elements without intervening mitosis in the previous study (Fukuda and Komamine 1980b), indicating that mitosis is not a prerequisite for cytodifferentiation.…”
Section: Discussionmentioning
confidence: 99%
“…and Malawer and Phillips A close relationship exists between cytodifferentiation (1979) observed that parenchytna cells in cultured and the cell cycle in eukaryotic organisms (Bishoff and explants of Jerusalem artichoke tubers differentiated Holtzer 1969, Fosket 1968, indicating that molecular into tracheary elements at the Gj phase after going mechanisms governing differentiation may be regulated through three rounds of the cell cycle, Shininger (1975) by DNA replication or mitosis. Important problems that suggested that DNA replication was a prerequisite for still remain unresolved are, however, whether or not tracheary element differentiation in pea root segments mitosis and/or DNA replication are really prerequisites because cytodifferentiatian was inhibited by for cytodifferentiation, and whether the precursor cells 5-fluorodeox)'uridine or 5-bromodeoxyuridine, On the become committed to the new pathway of cytodifferen-other hand, a few tracheary elements were formed in tiation after receiving stimulation to differentiation at the presence of 5-fluorodeoxyuridine in culttired lettuce some particular phase of the cell cycle, Xylogenesis in explants (Turgeon 1975), Since multicellular systems tissue and cell cultures is a useful model system for the were used for most studies of cytodifferentiation, the study of cytodifferentiation in plants (Roberts 1976), conclusions were tentative; in these systems, it was not possible to determine whether or not individual cells had in fact undergone tnitosis.…”
Section: Introductionmentioning
confidence: 97%